Education and the environment : policy, trends and the problems of marginalisation - Gough, Annette. (Australian Council for Educational Research, 1997)
The emergence of environmental education: a'history' of the field. Contemporary Australian policies on environmental education. Environmental education in a climate of educational change. Exploring alternative perspectives. Ongoing issues and challenges for the future.